Insight into the Formation of Glimepiride Nanocrystals by Wet Media Milling - Djordje Medarević; Svetlana Ibrić; Elisavet Vardaka; Miodrag Mitrić; Ioannis Nikolakakis; Kyriakos Kachrimanis (MDPI AG, 2020)
Nanocrystal formation for the dissolution enhancement of glimepiride was attempted by wet media milling. Different stabilizers were tested and the obtained nanosuspensions were solidified by spray drying in presence of mannitol, and characterized regarding their redispersibility by dynamic light scattering, physicochemical properties by differential scanning calorimetry (DSC), FT-IR spectroscopy, powder X-ray diffraction (PXRD), and scanning electron microcopy (SEM), as well as dissolution rate. Lattice energy frameworks combined with topology analysis were used in order to gain insight into the mechanisms of particle fracture. It was found that nanosuspensions with narrow size distribution can be obtained in presence of poloxamer 188, HPC-SL and Pharmacoat® 603 stabilizers, with poloxamer giving poor redispersibility due to melting and sticking of nanocrystals during spray drying. DSC and FT-IR studies showed that glimepiride does not undergo polymorphic transformations during processing, and that the milling process induces changes in the hydrogen bonding patterns of glimepiride crystals. Lattice energy framework and topology analysis revealed the existence of a possible slip plane on the (101) surface, which was experimentally verified by PXRD analysis. Dissolution testing proved the superior performance of nanocrystals, and emphasized the important influence of the stabilizer on the dissolution rate of the nanocrystals.